2020
DOI: 10.1016/j.tipsro.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatially fractionated radiotherapy (SFRT) targeting the hypoxic tumor segment for the intentional induction of non-targeted effects: An in silico study to exploit a new treatment paradigm

Abstract: Introduction: The possibility of intentionally triggering non targeted effects (NTEs) using spatially fractionated radiotherapy (SFRT) alone or combined with immunotherapy is an intriguing and fascinating area of research. Among different techniques for SFRT, stereotactic body radiotherapy targeting exclusively the central hypoxic segment of bulky tumors, (SBRT-PATHY) might trigger immunogenic cell death more efficiently. This in silico study aims to identify the best possible dosimetric trade-off for prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Also, concerning palliative RT, there was great concurrence for single fr treatments of 8–10 Gy [ 133 , 136 , 297 , 298 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, concerning palliative RT, there was great concurrence for single fr treatments of 8–10 Gy [ 133 , 136 , 297 , 298 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can deliver relatively high but different radiation doses over different fractions. It is distinguished by its steep dose gradient, which enables irradiation of the central hypoxic area of the tumor at high doses while preserving the function of surrounding tissues to elicit potent ICD ( Massaccesi et al, 2020 ).…”
Section: Icd Inducers and Molecular Mechanismmentioning
confidence: 99%
“…Piras, et al concluded, in their systematic review, that most papers found that the use of HFRT reduced times at the hospital, which decreased the potential for infection of all concerned [15,43,50,51]. Furthermore, most researchers found that single-fractionated treatments were preferred for palliative radiotherapy [13,[52][53][54]. Data has yet to be collected on the effectiveness of HFRT during the pandemic but a study from the Tata Memorial Center in Mumbai, India, indicated that, from 1 March 2020, through to 31 October 2020, 11,000 new patients were treated for cancer (a decrease of 63% from 2019) [6].…”
Section: Background On Hypofractionation and Use During The Pandemicmentioning
confidence: 99%